2020
DOI: 10.3390/ijms21031117
|View full text |Cite
|
Sign up to set email alerts
|

ITIH5 and ECRG4 DNA Methylation Biomarker Test (EI-BLA) for Urine-Based Non-Invasive Detection of Bladder Cancer

Abstract: Bladder cancer is one of the more common malignancies in humans and the most expensive tumor for treating in the Unites States (US) and Europe due to the need for lifelong surveillance. Non-invasive tests approved by the FDA have not been widely adopted in routine diagnosis so far. Therefore, we aimed to characterize the two putative tumor suppressor genes ECRG4 and ITIH5 as novel urinary DNA methylation biomarkers that are suitable for non-invasive detection of bladder cancer. While assessing the analytical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 42 publications
(59 reference statements)
2
16
0
Order By: Relevance
“…Several studies have shown that the ECRG4 promoter is frequently hypermethylated in patients with breast cancer, gastric cancer, and nasopharyngeal carcinoma, resulting in the downregulation of ECRG4 ( You et al, 2015 ; Deng et al, 2018 ; Tang et al, 2019 ). Consistent with a previous study that reported that ECRG4 is hypermethylated in BCa cells ( Rose et al, 2020 ), our results further demonstrated that ECRG4 is significantly downregulated in BCa tissues and cell lines. Furthermore, we observed that ECRG4 expression was positively correlated with OGN, which is a tumor suppressor in colorectal cancer and breast cancer ( Hu et al, 2018 ; Xu et al, 2019 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Several studies have shown that the ECRG4 promoter is frequently hypermethylated in patients with breast cancer, gastric cancer, and nasopharyngeal carcinoma, resulting in the downregulation of ECRG4 ( You et al, 2015 ; Deng et al, 2018 ; Tang et al, 2019 ). Consistent with a previous study that reported that ECRG4 is hypermethylated in BCa cells ( Rose et al, 2020 ), our results further demonstrated that ECRG4 is significantly downregulated in BCa tissues and cell lines. Furthermore, we observed that ECRG4 expression was positively correlated with OGN, which is a tumor suppressor in colorectal cancer and breast cancer ( Hu et al, 2018 ; Xu et al, 2019 ).…”
Section: Discussionsupporting
confidence: 93%
“…To date, many studies have focused on the upstream epigenetic regulation of ECRG4 and the promoter region of ECRG4, which is frequently hypermethylated in cancers, including BCa (Rose et al, 2020). However, few studies have been reported regarding the downstream regulation mechanism of ECRG4.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, ITIH5 might be of interest to develop novel panels of predictive biomarkers helping to stratify bladder cancer patients for (neo)adjuvant treatment. ITIH5 DNA methylation, which was shown to be useful as biomarker to detect bladder cancer via urine [ 24 ], may further hold information for predicting chemo-response of bladder cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…In bladder carcinogenesis, we previously demonstrated epigenetic inactivation of ITIH5 associated with advanced tumor stages predicting unfavorable prognosis of patients diagnosed with a papillary (pT1) urothelial high-grade tumor [ 20 ]. ITIH5 promoter methylation was also characterized as putative biomarker for non-invasive detection of breast [ 23 ] and bladder cancer [ 24 ] via plasma and urine samples, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…15 It has been clarified that promoter methylation of the tumor suppressor gene is often negatively correlated with its expression. 16 Demethylation treatment can significantly inhibit the malignant biological behavior of tumors. 17 The methylation degree of specific gene region is directly related to lymph node metastasis, TNM stage, tumor pathological classification and prognosis.…”
Section: Discussionmentioning
confidence: 99%